Chemical and Biological Investigations of Cerbera odollam Gaertn - Rahman, Monica Sharfin; Faisal, Adnan; Hasan, Choudhury Mahmood; Ahsan, Monira; Masud, Mohammad Mehedi (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The present article describes the isolation and characterization of secondary metabolites from the leaves of Cerbera odollam as well as bioactivities of the crude methanolic extract and its petroleum ether (PE), carbon tetrachloride (CTC), chloroform (CF) and aqueous (AQ) soluble fractions. In this investigation, successive chromatographic separation and purification yielded β-amyrin (CO-01), lupeol (CO-02), β-sitostenone (CO-03) and triticusterol (CO-04). The study also indicated the antioxidant, cytotoxic, antimicrobial, membrane stabilizing activities and poor thrombolytic activities. Thus, the present study endeavors to provide scientific basis to establish Cerbera odollam as a potential medicinal plant. Dhaka Univ. J. Pharm. Sci. 16(2): 179-186, 2017 (December)